Children’s literature and emotions: mother-child relationship - Balca, Angela (2020)
Children's literature allows us to consider texts where the motherchild relationship is not exempt from problems that bring out emotions of all kinds. In this sense, the objectives of the study are to understand how Children’s Literature problematizes the mother-child relationship; how Children’s Literature addresses the issue of emotions within the scope of this relationship; and discuss how Children’s Literature contributes to the social and emotional development of children. In order to achieve these goals, we have considered the works of authors and illustrators of several nationalities: The day mother had a face like a teapot (2008), by Raquel Saiz and João Vaz de Carvalho; Mama Robot (2007), by Davide Cali and Anna Laura Cantone; Tesla's mom doesn’t want to (2010), by Åsa Mendel-Hartvig and Caroline Röstlunf. Our methodology privileges the hermeneutical analysis of written texts and illustrations, making an exegesis thereof, through a critical and reflexive reading. From this analysis, we conclude that Children’s Literature depicts a mother-child relationship that is not free from conflict and negative emotions, but which are regulated and controlled, resulting in positive emotional states of affection and love between them.